(untitled) (Journal of Oriental Studies, 2017)
Japan is a country of rich cultural traditions. Such words as samurai, geisha and sakura are well-known among people, who are interested in this country. However, in the recent time there is another cultural phenomenon, which attracts people. It is Japanese comics called «Manga» 漫画）. Despite the fact that in these days publication of manga is a major part of the publishing industry, this type of mass media has its own long history. This article provides a definition of the word «Manga», refers differences as well as comparisons with Western comics. There are given some types of difficulties of translating manga with those interpreters are often faced to.